Effect of Carbohydrate Formulas on Instrumental and Sensory Parameters in Dry-Fermented Iberian Pork Sausages - Maite Sánchez-Giraldo; Montserrat Vioque-Amor; Rafael Gómez-Díaz; Ignacio Clemente-López; Manuel Ángel Amaro-López; Carmen Avilés-Ramírez (Foods)
Dry-fermented sausages are appreciated all over the world for their sensory characteristics. Carbohydrates (sugars) are added during the production process, the type and quantity of which directly affect the quality of this product. However, there are few data on the role of sugars on instrumental and sensory parameters of sausages derived from Iberian pork. The objective was to determine the effect of different carbohydrate formulas during the ripening time on the quality of dry-fermented Iberian pork sausages. Five batches were formulated with different combinations and concentrations of carbohydrates (dextrose, dextrin and glucose syrup), making 16 sausages per batch on which to perform repeated measurements throughout the ripening process. Physicochemical characteristics, instrumental colour, textural parameters and sensory attributes were analysed. The C− batch (without any carbohydrate addition) showed unstable pH evolution and high b* values throughout the ripening process and the lowest instrumental texture values (for hardness, springiness and chewiness). The D10d5 batch also presented an unstable pH evolution but low a* values, and it was the highest rated by consumers for sensory texture attributes. This batch, made with dextrose (in higher proportion) and dextrin, differed from the other Iberian pork sausages, suggesting that this carbohydrate formula may be more appreciated by Mediterranean consumers.